2018
DOI: 10.1177/1177271918806840
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers of B-cell Lymphoma

Abstract: B-cell lymphomas represent a diverse group of neoplasms classified primarily by histopatholgy and are often challenging to accurately diagnose. Despite having been recognized less than 20 years ago, microRNAs (miRNAs) have emerged as one of the most promising class of cancer molecular biomarkers and are particularly attractive as they can be readily detected in formalin-fixed paraffin-embedded biopsy material and biological fluids such as blood. Many of the identified B-cell lymphoma miRNA biomarkers also play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 177 publications
(231 reference statements)
2
24
0
1
Order By: Relevance
“…This is consistent with other studies that reported changes in miRNA composition in tissues distinct from the primary location of clinical disease [16,[21][22][23]. Previous studies have investigated miRNA profiles in non-Hodgkin lymphoma, most often the diffuse large B cell lymphoma subtype (DLBCL) [11,14,24]. DLBCL is a relative infrequent subtype of NHOL [2], reflected by only two cases in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with other studies that reported changes in miRNA composition in tissues distinct from the primary location of clinical disease [16,[21][22][23]. Previous studies have investigated miRNA profiles in non-Hodgkin lymphoma, most often the diffuse large B cell lymphoma subtype (DLBCL) [11,14,24]. DLBCL is a relative infrequent subtype of NHOL [2], reflected by only two cases in our study.…”
Section: Discussionsupporting
confidence: 93%
“…DLBCL is a relative infrequent subtype of NHOL [2], reflected by only two cases in our study. In contrast, the most frequent NHOL subtype in our study was extranodal marginal zone lymohoma (EMZL), for which serum miRNAs studies are rare [11,24]. Nonetheless, studies of lymphoma biopsies have shown an increased expression of miR-223 and miR-193 in EMZL [25], and a downregulation of miR-29a, miR-223, and miR-140 in DLBCL [26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…group of neoplasms classified primarily by histopathology and is often challenging to accurately diagnose. 2,3 More than half of the patients with B-cell NHL can achieve long-term remission; strikingly, the overall cure rate for some subtypes in developed countries is approximately 90%, especially DLBCL. However, these therapies are sometimes ineffective, particularly for patients with high-risk disease or late-stage diagnosis, or the rare malignant lymphoma, MCL.…”
Section: Introductionmentioning
confidence: 99%
“…Many miRNAs have been identified as biomarkers of B-cell lymphoma. 22 , 23 Schneider et al. 17 revealed that miR-28 expression is downregulated in B-cell lymphomas, suggesting that silencing of miR-28 will contribute to lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%